Comparison of success rates, learning curves, and inter-subject performance variability of robot-assisted and manual ultrasound-guided nerve block needle guidance in simulation. (23rd January 2014) - Morse, J.; Terrasini, N.; Wehbe, M.; Philippona, C.; Zaouter, C.; Cyr, S.; Hemmerling, T. M.
Abstract : Background: This study focuses on a recently developed robotic nerve block system and its impact on learning regional anaesthesia skills. We compared success rates, learning curves, performance times, and inter-subject performance variability of robot-assisted vs manual ultrasound (US)-guided nerve block needle guidance. The hypothesis of this study is that robot assistance will result in faster skill acquisition than manual needle guidance. Methods: Five co-authors with different experience with nerve blocks and the robotic system performed both manual and robot-assisted, US-guided nerve blocks on two different nerves of a nerve phantom. Ten trials were performed for each of the four procedures. Time taken to move from a shared starting position till the needle was inserted into the target nerve was defined as the performance time. A successful block was defined as the insertion of the needle into the target nerve. Average performance times were compared using analysis of variance. P <0.05 was considered significant. Data presented as mean (standard deviation). Results: All blocks were successful. There were significant differences in performance times between co-authors to perform the manual blocks, either superficial ( P =0.001) or profound ( P =0.0001); no statistical difference between co-authors was noted for the robot-assisted blocks. Linear regression indicated that the average decrease in time between consecutive trials for robot-assisted blocks of 1.8 (1.6) s was significantly ( P =0.007) greater than the decrease for manual blocks of 0.3 (0.3) s. Conclusions: Robot assistance of nerve blocks allows for faster learning of needle guidance over manual positioning and reduces inter-subject performance variability.